2013
DOI: 10.4168/aair.2013.5.5.283
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency and Asthma Severity in Adults From Costa Rica

Abstract: PurposeNon-classical actions of vitamin D as a cytokine are related to the immunopathology of asthma. Few studies have examined vitamin D levels and asthma severity in adults. The aim of this research was to assess the relationship between vitamin D levels, atopy markers, pulmonary function, and asthma severity.MethodsWe analyzed 25-hydroxyvitamin D levels in serum collected from 121 asthmatic adults from Costa Rica to investigate the association between vitamin D levels (categorized as sufficient, ≥30 ng/mL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 29 publications
4
35
2
5
Order By: Relevance
“…A similar finding had been stated by many studies with the same result on elderly asthmatic patients, where (79%) had lower than normal serum vitamin D at baseline [23]. These results confirm that vitamin D deficiency and insufficiency are extremely common in patients with asthma [26], and mostly pronounced in patients with severe and/or uncontrolled asthma [18]. Kamran et al found a high prevalence of vitamin D deficiency and insufficiency (88.10%) in adult patients with moderate to severe persistent asthma [27].…”
Section: Discussionsupporting
confidence: 79%
“…A similar finding had been stated by many studies with the same result on elderly asthmatic patients, where (79%) had lower than normal serum vitamin D at baseline [23]. These results confirm that vitamin D deficiency and insufficiency are extremely common in patients with asthma [26], and mostly pronounced in patients with severe and/or uncontrolled asthma [18]. Kamran et al found a high prevalence of vitamin D deficiency and insufficiency (88.10%) in adult patients with moderate to severe persistent asthma [27].…”
Section: Discussionsupporting
confidence: 79%
“…Conforme al sexo, la mediana de la concentración de VD no fue diferente (p = 0.713): en los hombres 16 ng/mL (RIC, 14-22) y en las mujeres 18 ng/mL (RIC, [13][14][15][16][17][18][19][20][21][22][23]. Respecto a la actividad física, la mediana fue mayor en quienes realizaban ejercicio en comparación con quienes no lo hacían (p = 0.004): 18 ng/mL La concentración de VD mostró correlación negativa con la edad (p =0.047) y positiva con la actividad física (p = 0.004), como se describe en el Cuadro 3.…”
Section: Resultsunclassified
“…En Costa Rica, 14 la deficiencia e insuficiencia de VD en su conjunto fue de 90 %, similar a la observada en nuestra investigación. En niños, un análisis realizado en varias ciudades de Colombia mostró una frecuencia de alteraciones en la concentración de VD, insuficiencia o deficiencia, en 8.9 a 29.8 % de los casos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Furthermore, among pregnant women, vitamin D intake was found to be independently positively associated with the prevalence of asthma throughout pregnancy [24]. Among studies assessing vitamin D by serum 25(OH)D levels, some have found inverse associations between vitamin D status and allergy [1], infections [4], asthma [6,25], while others have not [22,26]. Among intervention trials investigating the effects of vitamin D supplementation on respiratory conditions, inconsistent results have been found [27][28][29][30].…”
Section: Variable Sun Exposure-vitamin D Index Score <mentioning
confidence: 98%